Динаміка мотиваційної структури студентів вищих технічних навчальних закладів і значення цілепокладання у цьому процесі - Михайличенко, Валентина Євдокимівна; Грень, Лариса Миколаївна; Полянська, Вікторія Вікторівна (НТУ "ХПІ", 2011)
The dynamics of student cognitive motivation during studying and its transformation to professional is discussed in the article. It is shown that recognition of goal increases student motivation, their activity, probability of it achievement.
Keywords: мотивація; творчий потенціал; потреби студентів; цілепокладання